Immediate dense circumstellar environment of supernova progenitors caused by wind acceleration: its effect on supernova light curves. (24th April 2017) - Moriya, Takashi J.; Yoon, Sung-Chul; Gräfener, Götz; Blinnikov, Sergei I.
Abstract: Type IIP supernova progenitors are often surrounded by dense circumstellar media that may result from mass-loss enhancement of the progenitors shortly before their explosions. Previous light-curve studies suggest that the mass-loss rates are enhanced up to ∼0.1 M⊙  yr −1, assuming a constant wind velocity. However, the density of circumstellar media at the immediate stellar vicinity can be much higher than previously inferred for a given mass-loss rate if wind acceleration is taken into account. We show that the wind acceleration has a huge impact when we estimate mass-loss rates from early light curves of Type IIP supernovae by taking SN 2013fs as an example. We perform numerical calculations of the interaction between supernova ejecta and circumstellar media with a constant mass-loss rate but with a β-law wind velocity profile. We find that the mass-loss rate of the progenitor of SN 2013fs shortly before the explosion, which was inferred to be ∼0.1 M⊙  yr −1 with a constant wind velocity of 10 km s −1 by a previous light-curve modelling, can be as low as ∼10 −3  M⊙  yr −1 with the same terminal wind velocity of 10 km s −1 but with a wind velocity profile with β ≃ 5. In both cases, the mass of the circumstellar medium is similar (≃0.5 M⊙ ). Therefore, the beginning of the progenitor's mass-loss enhancement in our interpretation is ∼100 yr before the explosion, not several years. Our result indicates that the immediate dense environment of Type II supernova progenitors may be significantly influenced by wind acceleration.